Achieving Room‐Temperature Charge Density Wave in Transition Metal Dichalcogenide 1T‐VSe2. (13th March 2020) - Feng, Jiajia; Susilo, Resta A.; Lin, Bencheng; Deng, Wen; Wang, Yanju; Li, Bin; Jiang, Kai; Chen, Zhiqiang; Xing, Xiangzhuo; Shi, Zhixiang; Wang, Chunlei; Chen, Bin
Abstract: Charge density wave (CDW) systems have been widely studied and proposed to be potential candidates for next‐generation electronic devices. However, the lack of room‐temperature CDW materials has limited the development of CDW‐based electronic devices, and thus finding a way to manipulate the CDW transitions and orders toward room temperature will be of importance. Room‐temperature and above CDW transition in 1 T ‐VSe2 is reported. The CDW transition is found to shift to ≈114 K at 0.7 GPa, and further compression enhances the transition temperature dramatically, reaching ≈358 K at 14.6 GPa. High‐pressure Raman spectroscopy measurement confirms that room‐temperature CDW order is achieved and persists up to 15 GPa. Such significant enhancement in CDW can be attributed to the pressure enhanced out‐of‐plane Fermi surface nesting and CDW gap in 1 T ‐VSe2 . The observation of room‐ and high‐temperature CDW transition in 1 T ‐VSe2 under pressure provides an engineering approach to optimizing the CDW as needed in applications, which does not only open up a new platform for searching and controlling novel states of two‐dimensional materials, but also promotes a practical development of CDW‐related technology and devices. Abstract : Room‐temperature charge density wave (CDW) is obtained under high pressure. The progressively smaller axial ratio a/c of crystal structure enhances CDW gap and interlayer coupling, which is closely related to Fermi surface nesting and strongly enhances CDW transition temperature.